Pengaruh Intensitas Periklanan Media Sosial Terhadap Minat Beli melalui Citra Merek Sebagai Intervening - Yuliawati, Novi; Hurriyati, Ratih; Monoarfa, Hilda (Universitas Pendidikan Indonesia, 2024)
The importance of growing consumer buying interest to encourage decisions to purchase a product has attracted researchers' interest in investigating factors that can influence it. This research was conducted using quantitative methods with descriptive and verification approaches. The primary data came from the answers of respondents who were gathered using a non-probability sampling technique with a purposive sampling and convenience approach, while the secondary data were from the results of a literature study. The obtained data were then analyzed using the SEM-PLS analysis technique with the help of SmartPls 3 software. The research shows that the intensity of Instagram social media advertising has a direct, significant positive influence on Young Living's brand image. Brand image has a direct, significant positive influence on Young Living's buying interest. Instagram social media advertising intensity has no influence on Young Living buying interest, and brand image has a role in mediating the indirect influence of Instagram social media advertising intensity on Young Living buying interest with a significant positive value.